HUBUNGAN SPIRITUAL WELL-BEING DENGAN GEJALA MENOPAUSE - TULUS, ANGELINA; DARMAYASA, I MADE; ARIANI, NI KETUT PUTRI (HEALTHY : Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Spirituality has become an essential part of human life, yet it still raises various questions regarding its relationship with health. Spiritual well-being indicates a person’s quality of life in terms of spiritual dimensions or serves as an indicator of an individual’s spiritual health. In 2016, 7.4% of women in Indonesia were menopausal, and by 2020, this was projected to reach 11.54%, with an average menopause age of 49 years. The Study of Women's Health Across the Nation in the United States found that menopause is associated with psychological stress. Approximately 28.9% experienced stress in early perimenopause, 20.9% during perimenopause, and 22% post-menopause. Menopause triggers physical and psychological symptoms, causing women to experience various complaints. Good spiritual well-being is associated with lower anxiety and depression and a higher quality of life. Spiritual Well-Being (SWB) arises from a state of spiritual health and manifests as overall well-being. SWB is an indication of a person’s quality of life in terms of spiritual dimensions or an indicator of their spiritual health. The spiritual element has a positive relationship with emotional responses. Spirituality affects the limbic and autonomic nervous systems, creating pleasant feelings and stimulating GABA and endorphins. Spiritual experiences can influence neurotransmitters in the brain, such as serotonin, dopamine, and oxytocin. Serotonin and dopamine are linked to feelings of happiness and satisfaction, while oxytocin is associated with empathy and social interaction. Menopause is defined as one year without menstruation due to a decrease in estrogen production. Although some women are asymptomatic, estrogen deficiency can cause hot flushes, sweating, insomnia, and vaginal dryness and discomfort in nearly 85% of menopausal women. This state is often referred to as the “change of life.” Spirituality has a significant relationship with the severity of menopause symptoms, including mood, cognition, vasomotor, and sexual symptoms. Spiritual well-being is related to menopausal symptoms. ABSTRAKSpiritualitas telah menjadi bagian penting dalam kehidupan manusia, namun masih menimbulkan berbagai pertanyaan terkait hubungannya dengan kesehatan. Spiritual well-being atau kesejahteraan spiritual menjadi indikasi kualitas hidup seseorang dari segi dimensi spiritual atau indikasi dari kesehatan spiritual seseorang. Pada tahun 2016, di Indonesia terdapat 7,4% wanita menopause dari total populasi dan tahun 2020 diperkirakan mencapai 11,54% dengan usia rata-rata menopause 49 tahun. Hasil Study of Women’s Health Across the Nation di Amerika Serikat menunjukkan bahwa masa menopause berhubungan dengan tekanan psikologi. Sebanyak 28,9% mengalami stres diawal premenopause, 20,9% pada premenopause, dan sebanyak 22% pada post menopause. Menopause memunculkan gejala fisik maupun psikis yang membuat wanita mengalami berbagai macam keluhan. Kesejahteraan spiritual yang baik dikaitkan dengan kecemasan dan depresi yang lebih rendah, dan kualitas hidup yang lebih baik. Spiritual Well Being (SWB) adalah situasi yang muncul dari keadaan kesehatan spiritual dan tampak melalui kesehatan yang baik. SWB menjadi indikasi kualitas hidup seseorang dari dimensi spiritual atau indikasi dari kesehatan spiritual seseorang. Unsur spiritual memiliki hubungan positif terkait dengan respons emosional. Spiritualitas memengaruhi sistem limbik dan saraf otonom, sehingga menghasilkan suasana perasasan yang menyenangkan dan merangsang GABA dan endorfin. Pengalaman spiritual dapat memengaruhi neurotransmitter dalam otak seperti serotonin, dopamin, dan oksitosin. Serotonin dan dopamin terkait dengan perasaan bahagia dan kepuasan, sementara oksitosin terkait dengan empati dan interaksi sosial. Menopause didefinisikan sebagai satu tahun tanpa menstruasi dikarenakan semakin berkurangnya produksi estrogen. Meskipun beberapa perempuan asimtomatik, defisiensi estrogen dapat menyebabkan gejolak hot flushes, berkeringat, insomnia, kekeringan dan ketidaknyamanan pada vagina pada hampir 85% perempuan menopause. Keadaan ini sering disebut “change of life”. Spiritual memiliki hubungan signifikan pada keparahan menopause, yaitu dari gejala mood, kognisi, vasomotor dan seksual. Spiritual well-being memiliki hubungan dengan gejala menopause.